PENGARUH VARIASI TEMPERATUR HEAT TREATMENT TERHADAP KEMAMPUKERASAN BAJA KOMERSIL DENGAN METODE JOMINY TEST - Yusuf Yusuf; Asep Ruchiyat; Irwan Susilo (Politeknik Negeri Ketapang, 2021)
Hardenability is the ability of a material to be hardened to a certain depth by means of heat treatment to form martensite in the cooling process to achieve a certain hardness. One of the hardenability testing methods is the Jominy Test. The specimen is heated at the specified temperature, then cooled by spraying water at one end. After testing with the Jominy test apparatus, its hardness was measured using the hardness test equipment.The testing of Jominy is based on ASTM standard A255. Testing using specimens with a length of 100 mm, diameter 25.4 mm as much as 9 pieces. Hardness is measured by the Rockwell Hardness Test method. The test result on specimen 1 with a final temperature of 700 °c resulted in an average hardness value of 45.51 HRB, on specimen 9 with a final temperature of 1100 °c amounting to 47.32 HRB.